Collagen-Mediated Platelet Aggregation: The Role of Multiple Interactions between the Platelet Surface and Collagen - Santoro, Samuel A; Cunningham, Leon W (Thrombosis and Haemostasis, 1980)
Although the requirement for collagen fibrils to initiate platelet aggregation is well established, there has been no satisfactory explanation for this requirement. One possibility is that multiple simultaneous and linked interactions between collagen and the platelet surface must occur to initiate the release reaction and subsequent aggregation.Direct evidence in support of this proposal was obtained by examination of the ability of collagen crosslinked in a random manner with glutaraldehyde to initiate platelet aggregation. Collagen crosslinked with 0.25 % glutaraldehyde is only a slightly less effective aggregating agent than native fibrillar collagen. Further studies revealed that whereas native triple helical cross-linked collagen is an effective aggregating agent, denatured crosslinked collagen is ineffective.It thus appears that crosslinking of platelet receptor sites by multiple simultaneous and linked interactions with a rigid collagen matrix is required to initiate platelet aggregation. The precise steric relationship of the collagen sites does not appear to be of great importance.
Keywords: Platelets; Collagen; Multiple interactions